Going beyond common motivational strategies and teaching styles - Riandi, Riandi (Diksi, 2022)
This paper aims to determine the styles of teaching and motivational strategies carried out by two teachers in Frank McCourt's Teacher man (McCourt, 2005) and School of Rock, a film (Linklater, 2003). The comparative method is used in this study as an effort to take a scientific approach on literary works. The researcher sorted, dissected, and compared literary works in different settings to make meaning, to convey their feelings, sentiments, and concepts to the author himself as a reader. Based on the findings, teachers in Frank McCourt's Teacher man (McCourt, 2005) and School of Rock, a film (Linklater, 2003) make their students interested in the material being discussed in class they are more likely to channel their own internal motivation towards education and end up learning more. Teaching beyond the curriculum standards should be viewed as incredible opportunity to create meaningful lessons that will capture the attention of all students. Keywords: motivational strategies, teaching styles, teaching